Infinite Horizon Optimal Control of Stochastic Delay Evolution Equations in Hilbert Spaces - Xueping Zhu; Jianjun Zhou (Abstract and Applied Analysis)
The aim of the present paper is to study an infinite horizon optimal control problem in which the controlled state dynamics is governed by a stochastic delay evolution equation in Hilbert spaces. The existence and uniqueness of the optimal control are obtained by means of associated infinite horizon backward stochastic differential equations without assuming the Gâteaux differentiability of the drift coefficient and the diffusion coefficient. An optimal control problem of stochastic delay partial differential equations is also given as an example to illustrate our results.